Dynamic susceptibility of Fe3O4 nanotubes - Pusiol, Enzo Fabrizio (2023)
In this work we performed a detailed numerical analysis to investigate the dynamic susceptibility of 1000 nm long Fe3O4 nanotubes by varying the diameter, the tube wall thickness and the magnitude of the external magnetic field applied along the tube axis. We found two well-defined modes, one of low frequency associated with the caps of the nanotubes, and another of high frequency associated with the central area of the nanotubes, which can be controlled by varying the geometry of the tubes or the external magnetic field to which they are subjected. These results allow us to suggest the use of these nanotubes in applications that require controlling the resonant frequency in the GHz range.